1972
DOI: 10.1002/jcp.1040790306
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenesis of embryonic chick skeletal muscle cells differentiated in vitro

Abstract: Electrogenesis of embryonic chick skeletal muscle cells differentiated in monolayer cultures was investigated. Muscle fibers in uitro generate spike potentials similar to those of fibers in wino. However, other responses, plateaux resembling those i n heart muscle, are also elicited. These results suggest that a functional differentiation exists i n cultured muscle fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
1

Year Published

1973
1973
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 14 publications
1
17
1
Order By: Relevance
“…A prolonged AP outlasting the stimulating pulse by several seconds has been described in embryonic chick myotubes in culture (18,24) and in situ (17). During development in situ this response appears before the fast AP and disappears after hatching (17 (25).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A prolonged AP outlasting the stimulating pulse by several seconds has been described in embryonic chick myotubes in culture (18,24) and in situ (17). During development in situ this response appears before the fast AP and disappears after hatching (17 (25).…”
Section: Discussionmentioning
confidence: 96%
“…The expression of these properties is autonomously regulated with no requirement for neuronal intervention. Although a rise in RP during differentiation of myotubes has been reported in culture (13)(14)(15) and in situ (16,17), low synchrony in differentiation produced large variability in electrical responses (17,18) and has hampered determination of the time of appearance and sequence of development of membrane excitability. Fischbach et al (13) The development of contractile activity is indicated by the early appearance of local twitches, which spread through the entire myotube upon maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work has demonstrated a relationship between the mechanical activity of myotubes and the accumulation of muscle protein (10,(19)(20)(21) . In chick myotubes cultured in the presence of 1 p,M tetrodotoxin (TTX), early development proceeds normally, but by 5-6 d, when normal cultures are exhibiting spontaneous contraction, TTX cultures exhibit little or no mechanical activity and contain only 50% the myosin of control cultures (21).…”
mentioning
confidence: 99%
“…electrical properties of myotube membranes (8,10) . Newly formed myotubes exhibit a resting potential of -15 mV which increases to -60 mV as the myotube matures (8,14).…”
mentioning
confidence: 99%
“…et a!., 1971; KANO et al, 1972KANO et al, , 1977RITCHIE and FAMBROUGH, 1975;SPECTOR and PRIvEs, 1977) and the culture of an established myogenic cell line (LAND et al, 1973;KIDOKORO, 1973KIDOKORO, , 1975. Of these, the clonal cell line would offer an advantageous system for these studies because of its homogeneous cell population and synchronism of differentiation.…”
mentioning
confidence: 99%